2021
DOI: 10.1021/acs.jpca.0c08029
|View full text |Cite
|
Sign up to set email alerts
|

Negative Singlet–Triplet Excitation Energy Gap in Triangle-Shaped Molecular Emitters for Efficient Triplet Harvesting

Abstract: The full harvesting of both singlet and triplet excitons can pave the way towards more efficient molecular light-emission mechanisms (i.e., TADF or Thermally Activated Delayed Fluorescence) beyond the spin statistics limit. This TADF mechanism benefits from low (but typically positive) singlet-triplet energy gaps or ∆E ST . Recent research has suggested the possibility of inverting the order of the energy of lowest singlet and triplet excited-states, thus opening new pathways to foster light emission without a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
101
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 75 publications
(105 citation statements)
references
References 91 publications
4
101
0
Order By: Relevance
“…Furthermore, we note how the S 1 ← S 0 excitation energies are overestimated (severely in the case of 7AP) by both methods with respect to experimental or SCS-CC2 reference results. Note that many previous publications [14][15][16][17][18][19][20][21] already demonstrated how this was the case for all exchange-correlation functionals assessed up to now, which is also confirmed here.…”
Section: Td-dft Calculationssupporting
confidence: 89%
See 2 more Smart Citations
“…Furthermore, we note how the S 1 ← S 0 excitation energies are overestimated (severely in the case of 7AP) by both methods with respect to experimental or SCS-CC2 reference results. Note that many previous publications [14][15][16][17][18][19][20][21] already demonstrated how this was the case for all exchange-correlation functionals assessed up to now, which is also confirmed here.…”
Section: Td-dft Calculationssupporting
confidence: 89%
“…Therefore, theoretical methods based on one-electron excitations (i.e., Time-Dependent Density Functional Theory or TD-DFT) are questioned in its current implementation to recognize that excited-state energy inversion, due to the lack of inclusion of higher-thansingle excitations into their formulation. In contrast, wavefunction methods have been shown in recent studies [14][15][16][17][18][19][20][21] to provide reasonably accurate values for that ∆E ST energy difference, although at a cost certainly higher than TD-DFT.…”
Section: Introductionmentioning
confidence: 92%
See 1 more Smart Citation
“…Furthermore, several strategies for designing MR-TADF molecules have been presented, such as boron-nitrogen (BN) type [18][19][20][21], boron-oxygen type [19,22,23], and boron-carbonyl type [21,24]. Moreover, heterodoped MR-TADF emitters with triangulene backbone of different sizes have been reported [25][26][27][28][29][30]; researchers also synthesized the graphene-like BN-MR-TADF blue molecules B2 and B3 (Figure 1c,d), which are also promising blue TADF materials with small ∆E ST (0.15-0.18 eV) and narrow FWHM (32-34 nm) [31]. The representative MR-TADF compounds are a new class of polycyclic aromatic compounds, designed with fused planar structures containing boron and nitrogen (or oxygen).…”
Section: Introductionmentioning
confidence: 99%
“…11 Sancho-Garcia and co-workers have suggested that small chemical modifications of the triangle derivatives can produce good candidates for inverted singlet-triplet gap using several correlated wave function methods. 13,19 While many wave function-based electronic structure methods, such as configuration interaction singles with doubles correction (CIS(D)) 20 , EOM-CCSD 18 and similarity transformed equation-of-motion coupled-cluster singles and doubles (STEOM-CCSD) 21,22 , have predicted inverted singlet-triplet gaps qualitatively correctly, one of the most widely used excited-state electronic structure method, linear response time-dependent density functional theory (LR-TDDFT) 23 has failed to predict the inversion of singlet-triplet gaps.Computational studies, in the past, pointed towards the inability of LR-TDDFT to incorporate double excitations by going beyond adiabatic approximation 24 as the source of this error. 10…”
mentioning
confidence: 99%